Stochastic modelling to predict a priori the potential outcomes of different control schemes against the cattle tick Rhipicephalus microplus - Miotti, Camila (2024)
Stochastic models are valuable tools to describe and analyze tick population dynamic in a given area, and to evaluate different control schemes. The objective of this study was to provide a tool to predict a priori how a control scheme could affect the abundance of Rhipicephalus microplus in an area highly favourable for its development, through the building of a stochastic model of the population dynamic of this tick. The dynamic was stochastically modelled using field data of the parasitic and non-parasitic phases of R. microplus. The host susceptibility to tick infestations was also considered by including representative values of natural resistance of three different breeds (Bos indicus, B. taurus and B. indicus x B. taurus). Two different control schemes (strategic and threshold methods) using three annual applications of synthetic acaricides in different moments were evaluated. Furthermore, we have evaluated the impact of different moments of pasture spelling as a tool for tick control on the dynamic of the non-parasitic phases of R. microplus. The results showed that the model appropriately fits to field data and can simulate the annual variability in female ticks count in animals from different ecological characteristics. The model has also captured the variability that host susceptibility has on tick abundance. This fact was expressed in the different levels of tick abundance obtained for the three breeds of bovines. According to the model, strategic control applications of chemical acaricides have more efficacy than the threshold control method. The model indicates that a pasture spelling started in early or mid-summer generates a higher reduction in the number of available eggs in pastures. Analysis of the results allows to conclude that the model developed in this study was useful to predict a priori the performance of different control methods based on the strategic application of chemical acaricides or by applying pasture spelling.